Programmed cell death 4 and microRNA 21 inverse expression is maintained in cells and exosomes from ovarian serous carcinoma effusions. Issue 9 (28th May 2014) - Cappellesso, Rocco; Tinazzi, Andrea; Giurici, Thomas; Simonato, Francesca; Guzzardo, Vincenza; Ventura, Laura; Crescenzi, Marika; Chiarelli, Silvia; Fassina, Ambrogio
<x xml:space="preserve">Abstract</x> BACKGROUND Ovarian serous carcinoma (OSC) is a fatal gynecologic malignancy usually presenting with bilateral localization and malignant peritoneal effusion. Programmed cell death 4 (PDCD4) is a tumor suppressor gene whose expression is directly controlled by microRNA‐21 (miR‐21). Exosomes are small cell‐derived vesicles that participate in intercellular communication, delivering their cargo of molecules to specific cells. Exosomes are involved in several physiological and pathological processes including oncogenesis, immunomodulation, angiogenesis, and metastasis. The current study analyzed the expression of PDCD4 and miR‐21 in resected OSC specimens and in cells and exosomes from OSC peritoneal effusions. METHODS PDCD4 was immunohistochemically examined in 14 normal ovaries, 14 serous cystadenoma (CA), and 14 OSC cases. Quantitative reverse transcriptase‐polymerase chain reaction analysis of PDCD4 and miR‐21 expression was performed in CA and OSC cases and in cells and exosomes obtained from 10 OSC and 10 nonneoplastic peritoneal effusions. miR‐21 was also evaluated by in situ hybridization. RESULTS Immunohistochemistry demonstrated a gradual PDCD4 loss from normal ovaries to CA and OSC specimens. Quantitative reverse transcriptase‐polymerase chain reaction displayed higher PDCD4 messenger RNA levels in CA specimens compared with OSC cases and highlighted miR‐21 overexpression in OSC specimens. In situ hybridization detected miR‐21 only in OSC cells. This PDCD4 and miR‐21 inverse expression was also noted in cells and exosomes from OSC peritoneal effusions compared with nonneoplastic effusions. CONCLUSIONS PDCD4 and miR‐21 are involved in OSC oncogenesis. The transfer of miR‐21 by exosomes could promote oncogenic transformation in target cells distant from the primary tumor without direct colonization by cancer cells and could be used as a diagnostic tool. Cancer (Cancer Cytopathol) 2014;122:685–693. © 2014 American Cancer Society.